ÖĞRETMEN ADAYLARININ ÖZYÖNETİMLİ ÖĞRENMEYE İLİŞKİN HAZIRBULUNUŞLUKLARININ İNCELENMESİ. - KIRILMAZKAYA, Gamze (Electronic Turkish Studies)
In the constructivist approach which is under the influence of the education programs is defined as "The person learning with the learner". According to this definition, teachers need to have more professional knowledge and skills than in previous years. According to this teachers are expected to have certain features and skills. As knowledge rapidly increases and individuals face increased learning needs self-directed learning through teacher education and in the development of teacher training programs. Therefore teacher candidates who will teach you your future have self-directed learning skills and students are expected to gain this skill. This work it is important in terms of revealing the necessity of educating self-directed individuals. In this study, it is aimed to research whether the pre-service teachers' level of self-directed learning differs according to gender and department type variables. In this study using quantitative research method, the survey method of descriptive research methods used. The sample of the study is formed 337 preservice teachers, 113 male and 224 female students, who are educated in Science, Elemantary, Painting and Music teachers programs of the education faculty of a state university in 2016-2017 school year. Random sample selection method was applied when sampling was selected. Self -Directed Learning Readiness Scale was took in the study to determine the readiness of students to self-directed learning. With respect to the results of the study, it was assigned that self-directed learning readiness of preservice teacher was moderate. It was stated that pre-service teachers' self-directed learning levels did not differ in gender and department basis. In the findings obtained, comments were made about the self-directed learning levels of preservice teachers and some suggestions were presented in this regard.